Arthur and the popularity test - Krensky, Stephen (Brown, Marc Tolon. Marc Brown Arthur chapter book ;, 1998)
After Fern and Sue Ellen take a popularity test in a magazine for teenage girls, the two start changing, leaving their friends longing for the old Fern and Sue Ellen to return.